STRATEGIES FOR HUMAN RESOURCE MANAGEMENT IN THE DIGITAL ERA FOR GUANGXI UNIVERAITIES - Tao, Long; Suteeniran, Niran; Dejhome, Pachara; Wimuttipanya, Jittawisut (Journal of MCU Nakhondhat, 2024)
This research study aims to study and analyze the current situation of business management in agricultural campuses. Guangxi University In order to create guidelines for managing university affairs on this campus effectively. Data were collected from 269 campus managers from 4 different universities using a variety of research tools such as surveys, interviews, and evaluations. To provide a variety of information The results of the analysis help show that The situation in the agricultural campus is moderate. But it still has the potential for significant development and improvement. This results in a management approach that can effectively promote the development of the enterprise. This study is important in creating a deeper understanding of the current conditions and development trends. that can affect the development of agricultural business in the future This study is also important in supporting the development of agricultural campuses into truly efficient and reliable organizations. By focusing on analysis and presenting effective and reliable management solutions. This will help promote Guangxi University to be a leader in developing agricultural and management potential on this campus in the future. This is an important step in creating plans and strategies that will help drive future agricultural operations sustainably and efficiently. and affect the development of agricultural business in the future To create efficiency and foster a better situation on the agricultural campus in the long term and to utilize it in appropriate ways for future innovative development.